2020
DOI: 10.1177/0284185120936271
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of contrast-enhanced breast MRI versus X-ray mammography in women with different degrees of breast density

Abstract: Background Detection of breast cancer in women with high breast densities is a clinical challenge. Purpose To study the influence of different degrees of breast density on the sensitivity of contrast-enhanced breast magnetic resonance imaging (CE-BMRI) versus X-ray mammography (XRM). Material and Methods We performed an additional analysis of two large Phase III clinical trials (G1; G2) which included women with histologically proven breast cancers, called “index cancers.” Additional cancers were detected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The main techniques used for identification of breast lesions are ultrasound, mammography, and magnetic resonance imaging (MRI). MRI offers better sensitivity and specificity than mammography and ultrasonography, especially for lesions in dense breasts ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main techniques used for identification of breast lesions are ultrasound, mammography, and magnetic resonance imaging (MRI). MRI offers better sensitivity and specificity than mammography and ultrasonography, especially for lesions in dense breasts ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…High breast density is a common risk factor for breast cancer. Dense breasts have a 2.92–4.24 times higher risk of breast cancer than fatty breasts 21,22 . Not only do high‐density breasts have a low contrast with lesions, but the superposition of dense breast tissue reduces the sensitivity of mammographic diagnosis significantly 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Dense breasts have a 2.92–4.24 times higher risk of breast cancer than fatty breasts. 21 , 22 Not only do high‐density breasts have a low contrast with lesions, but the superposition of dense breast tissue reduces the sensitivity of mammographic diagnosis significantly. 23 Multiple studies have shown that the sensitivity of mammography to breast cancer decreases with increasing breast density.…”
Section: Discussionmentioning
confidence: 99%
“…The main results 6 and analyses by breast density were published elsewhere. 27 The evaluation was done on a pooled database of 2 large Phase III studies.…”
Section: Discussionmentioning
confidence: 99%